PARASITE INFECTIONS IN POULTRY ENVIRONMENTS (CASE REPORT ON GALLUS DOMESTICUS ENDOPARASITE) - Tanuwijaya, Phebe Amadea; Febraldo, David (UI Scholars Hub, 2021)
Infection of nematode and cestode worms in chickens can cause decreased egg production, weight loss, growth problems, weakness. The objective of this case study is to look at how an epidemiological approach, clinical symptoms, anatomical pathology investigation, and laboratory testing might help with disease diagnosis. The chicken was found from Banjar Tanggahan Tengah, Bangli, Bali with the type of native chicken (Gallus domesticus), at least 3 months old with the protocol number 369 / N / 20. Samples taken were brain, trachea, lungs, liver, heart, spleen, kidneys, proventriculus, intestines, and feces. Laboratory examinations carried out include histopathology, microbiology, and parasitology. The results of the pathological examination of the case showed that there was bleeding in the lobes of the lungs and liver, heart, brain, and trachea, there was edema, the small intestine and cecum had bleeding and mucosal enteritis, the spleen was depleted, the proventriculus was inflamed. Microbiology laboratory test results with the culture of organ samples identified by Escherichia coli bacteria. The results of fecal and microscopic parasite examinations found eggs and worms of the nematodes Ascaridia galli, Heterakis gallinarum, Capillaria caudinflata, Tetrameres americana, cestode Raillietina sp., And oocyst Eimeria sp. the protozoan digestive system. It is recommended that farmers improve cage sanitation and maintenance management for better poultry environments. Thus, the chickens would not easily infect by endoparasites.